Predictive Capacity of ACEF Score to Detect All-Cause Mortality and Post Contrast Acute Kidney Injury Among PCI Patients - Karki, Parag; Maskey, Arun; Timalsena, Birat Krishna; Poudel, Samir Kumar; Gautam, Binayak; Pant, Shambhu; Budhathoki, Lee (Nepalese Heart Journal, 2020)
Background and Aims: ACEF score is simple risk score which uses only three parameters for predicting mortality and postcontrast acute kidney injury (PC-AKI). This study was designed to look into various risk factors and ACEF score for patients undergoing Percutaneous Coronary Intervention (PCI). Methods: This is single-centre, observational, cross-sectional study. The patients were divided into tertiles.Bivariate analysis of various risk factors and ACEF score was done for PC-AKI as well as In-hospital and 30-day mortality. Results: Total 257 patients were included.The total mortality among PCI patients were low: In-hospital (0.8%) and 30-day (1.9%). The risk factor for increased mortality were higher Killip class and reduced Ejection Fraction (EF). PCAKI occurred in one-fifth. The risk factors for PC-AKI were increasing age, higher Killip class, diabetes, reduced EF, emergency PCI procedure and higher contrast volume. Hydration with NS was protective against PC-AKI. Mean ACEF score was higher among those who died within 30 days (p=0.35) and who developed PC-AKI (p<0.001). ACEF-low had trend toward better outcome with no mortality (p=0.17) and had low risk of PC-AKI (p=0.026). ACEF-moderate had reduced risk of PC-AKI (p=0.029), however was not associated with increased odds of 30-day mortality (p=0.66). ACEF-high showed significantly increased odds of mortality (p=0.04) and PC-AKI (p<0.001). Discriminatory capacity of ACEF score to detect 30-day mortality was good (AUC 0.82, p= 0.016) and goodness of fit=0.70. Discriminatory capacity of ACEF score to detect PC-AKI was fair (AUC 0.7, p<0.001) and goodness of fit=0.62. Conclusions: ACEF score fairly predicts the short-term mortality and PC-AKI in patients undergoing PCI.